The ice phenology as a predictor of Planktothrix rubescens bloom in vegetation season in temperate lakes - Lenard, Tomasz; Ejankowski, Wojciech (Frontiers in Microbiology, 2024)
Global warming affects air and water temperatures, which impacts the phenology of lakes and aquatic ecosystems. These changes are most noticeable during winter, when the potentially toxic Planktothrix rubescens forms its inoculum for annual blooms. Mostly, research has been conducted on alpine lakes, where blooms have persisted for decades, while a few have focused on temperate lakes. Our study aimed to determine the factors influencing the dynamics of the development of P. rubescens in temperate lakes where blooms occasionally occur, with a particular emphasis on the role of ice phenology.We investigated the vertical distribution of P. rubescens in an annual cycle in three temperate lakes. Samples were collected monthly in the winter and biweekly during the vegetative seasons. Overall, 434 samples were collected and analyzed according to biological and chemical parameters. Physical parameters were measured in situ.The vegetation seasons in temperate lakes showed a similar development pattern in the P. rubescens population as that in alpine lakes. Our results also show the influence of physical and chemical factors on the vertical distribution of this cyanobacterium. These results revealed the significant impact of P. rubescens filaments on phytoplankton biodiversity and biomass. Our data show the role of ice phenology in the establishment of the winter inoculum of P. rubescens and its further mass development until its disappearance in autumn.A climate-zone-independent pattern of P. rubescens blooms was observed during the vegetation periods. The population of P. rubescens was more influenced by physical factors than by the availability of dissolved nutrients in the water. Despite the same etiology, global warming has been shown to cause different responses in aquatic ecosystems, which affect the different nature of P. rubescens appearances. We associated blooms in temperate lakes, in contrast to alpine lakes, mainly with the presence of ice cover during severe winters, when the species establishes its inoculum. Hence, blooms in temperate lakes occur at different time intervals. Therefore, the dynamics of periodic blooms of P. rubescens in temperate lakes provide novel knowledge to the case study and a counterpoint to permanent blooms found in deep alpine lakes.